Endoscopic treatment of glottic stenosis secondary to caustic injury with silastic keel placement: A case report - Balachandran, Rekha; Rahmat, Omar (Malaysian Medical Association, 2011)
The use of an endoscopic approach for the division of glottic webs or stenosis has been reported in the literature and has been mainly confined to the anterior commisure. We report a rare case of caustic injury to the upper aerodigestive tract that resulted in extensive web formation along the membranous vocal cord which was successfully treated with endoscopic lysis of the adhesions and the use of a silastic sheet keel as a stent.